2021
DOI: 10.3390/v13061071
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of an Infectious Clone of Banana Streak CA Virus in A-Genome Bananas (Musa acuminata ssp.)

Abstract: We have characterized the complete genome sequence of an Australian isolate of banana streak CA virus (BSCAV). A greater-than-full-length, cloned copy of the virus genome was assembled and agroinoculated into five tissue-cultured plants of nine different Musa acuminata banana accessions. BSCAV was highly infectious in all nine accessions. All five inoculated plants from eight accessions developed symptoms by 28 weeks post-inoculation, while all five plants of M. acuminata AA subsp. zebrina remained symptomless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Our results concurred with that of Umber et al [25], that found higher prevalence of BSV in AAB than in AAA genotypes on field and of De Clerck et al [41] during indexing in greenhouse. This higher proportion could be due to the activation of BSV genomes (eBSOLV, eBSIMV and eBSGFV) integrated in the Musa B genome [21] and not the consequence of a horizontal transmission in field. These three BSV species were detected in this study together with BSCAV and BSMyV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results concurred with that of Umber et al [25], that found higher prevalence of BSV in AAB than in AAA genotypes on field and of De Clerck et al [41] during indexing in greenhouse. This higher proportion could be due to the activation of BSV genomes (eBSOLV, eBSIMV and eBSGFV) integrated in the Musa B genome [21] and not the consequence of a horizontal transmission in field. These three BSV species were detected in this study together with BSCAV and BSMyV.…”
Section: Discussionmentioning
confidence: 99%
“…There are up to 20 different virus species reported to infect banana worldwide [1] causing different symptoms. For instance, banana streak viruses cause leaf chlorosis, necrotic streaks on leaves, stuntedness, fruit distortion, smaller bunches and splitting pseudostem, which leads to death of infected plants [19,20,21]. and Banana streak PE virus (BSPEV) [22].…”
Section: Introductionmentioning
confidence: 99%